Status and associations of transition shock among nursing students during clinical practice: A cross-sectional study - Yinying Tang; Xiuwen Chen; Yuying Liao; Tingyu Zheng; Yao Xiao; Yunhui You (PLoS ONE, 2025)
Aim This study aimed to investigate the current state and influencing factors of transition shock among nursing students during clinical practice. Background Transition shock among nursing students can significantly impact their academic performance and well-being. Understanding the key factors contributing to this shock is crucial for developing effective support strategies and improving overall educational outcomes. Methods This cross-sectional study was conducted on October 8–28, 2022 at four tertiary Class A hospitals in Changsha, Hunan Province, located in south-central China. A convenience sample of 620 full-time nursing students was surveyed to collect demographic information and assess their transition shock levels using the transition shock scale. Data analysis included descriptive statistics, nonparametric tests, correlation analysis, and multiple regression. STROBE checklist was used for the methodology in this study. Results A total of 564 nursing students were ultimately included in the study. The average overall transition shock score was 46 (41, 52). Attitude toward the nursing profession had an independent influence on nursing students’ transition shock (p < 0.05). Additionally, the number of night shifts, choosing nursing as the first choice, being class leaders, education level, future plans, school scale, and monthly household income contributed to different dimensions of transition shock (p < 0.05). Conclusion and implications for nursing policy Nursing students experience moderate transition shock, with attitude towards nursing as a key influencing factor. Clinical managers should implement targeted measures to better support nursing students improve their attitudes.